Caribbean Tourism Development Programme. - NEEDHAM, Paul (1995)
Describes the three-year ECU 9 million programme which was launched by the European Union in 1993. The objectives of the programme were to achieve long-term growth in tourism earnings and visitor arrivals from Europe, improve tourism products to match European market needs, and promote smaller destinations.